Effect of two drying methods on chemical transformations in flue-cured tobacco. Issue 1 (2nd January 2022) - Zong, Jijian; He, Xian; Lin, Zhonglong; Hu, Mengyang; Xu, Anchuan; Chen, Yi; Zhao, Gaokun; Hu, Binbin; Jin, Yan; Zou, Congming
Abstract: Tobacco leaves are flue-cured to create desired appearance and internal quality, but the effects of flue-curing on transformation of chemical substances in tobacco have not been fully studied. The half-leaf method and a mass balance approach were used to compare two drying methods (i.e., oven-drying and flue-curing) in terms of chemical substances in tobacco. These substances included: carbon, nitrogen, plastid pigments, and polyphenols and some important elements in tobacco leaves. Compared with oven-drying, starch content significantly decreased while saccharides (including total sugar, glucose, fructose, maltose, and sucrose) increased in flue-cured tobacco leaves. There was only numerical change in reducing-sugar content between two drying methods. Protein, total nitrogen, and nicotine content in flue-cured tobacco leaves significantly decreased compared to oven drying. Two important elements (potassium and chlorine) showed no significant change. Compared with oven-drying, four plastid pigments (lutein, chlorophyll A, chlorophyll B, β-carotene) significantly decreased and six polyphenol substances (neochlorogenic acid, chlorogenic acid, caffeic acid, chrysatropic acid, rutin, kaempferol) significantly increased. This research clarified the transformation mechanisms of chemical substances after flue-curing of tobacco leaves, which provides a reference for the transformation and an insight into the procedures to study flue-cured tobacco leaf processing.